Chiral halogen and chalcogen bonding receptors for discrimination of stereo- and geometric dicarboxylate isomers in aqueous media. Issue 77 (10th September 2018) - Lim, Jason Y. C.; Marques, Igor; Félix, Vítor; Beer, Paul D.
Abstract : Dicarboxylate isomer discrimination and fluorescence sensing properties of a chalcogen bonding receptor differs considerably from halogen and hydrogen bonding analogues. Abstract : Novel chiral halogen and chalcogen bonding receptors exhibit different selectivities for stereo- and geometric dicarboxylate isomers compared to a hydrogen bonding analogue. The unique geometric and electronic properties of the chalcogen bonding receptor facilitate the diagnostic fluorescence sensing of geometric dicarboxylate isomer guest species.